White Mask and Yellow Face of Olivia’s CharacterIn Amy Tan’s The Hundred Secret Senses - DIANA SUSMAKER (LITERA KULTURA : Journal of Literary and Cultural Studies, 2013)
Ketika generasi kedua dari imigran China tinggal di negara multikultural seperti Amerika, mereka harus siap untuk menerima konsekuensi menghadapi kenyataan bahwa mereka terlahir untuk memiliki dua budaya. Generasi kedua dari immigran tersebut biasanya mengalami kesulitan untuk mengetahui kebudayaan mereka sebelumnya karena mereka menganggap dirinya sebagai bagian dari negara dimana mereka dilahirkan. Pengaruh dari dua kebudayaan, antara China dan Amerika membuat generasi kedua membentuk hibriditas identitas kebudayaannya. Bagaimanapun, hibriditas selalu dihubungkan dengan kekuasaan dua budaya yang memiliki kekuatan yang sama. Kedua budaya tersebut sangat kuat dan mengambil peranan dalam pembentukan identitas kebudayaan yang ganda. Dengan latar belakang seperti itu, maka permasalahan-permasalahan muncul seperti (1) bagaimana budaya Amerika dan China membentuk karakter Olivia dalam novel The Hundred Secret Sensesr karya Amy Tan? Dan (2) bagaimana hibriditas direfleksikan pada karakter Olivia dalam novel The Hundred Secret Sensesr karya Amy Tan? Metode yang digunakan adalah deskriptif kualitatif, hibriditas sebagai teori utama, konsep budaya, identitas budaya, nilai budaya China dan Amerika dan orientalisme sebagai teori pendukung. Hasil yang didapatkan akan menjelaskan bahwa generasi kedua dari immigran China yang tinggal di Amerika mampu mengetahui budaya orang tua yang dimilikinya melalui nilai-nilai budaya dari Negara tersebut dan pengasruh orang lain yang berhubungan dengan budaya orang tuanya.Kata Kunci: identitas budaya, generasi kedua, pembentukan, kekuasaan, hibriditas.AbstractWhen second generation of Chinese immigrants live in the multicultural country like America, the have to be ready to accept the consequences to face the reality that they were born to be hybrid. Second generation of immigrant may get difficult to recognize their former culture because they supposed their self as the member of the country where they were born. The influence of the two different cultures, between China and America may trace the second generation to consolidate their hybrid cultural identity. However, hybridity is always connected with the power of two different cultures which has the same power. Both of cultures is very strong and take an action in the process of reshaping hybrid cultural identity. All those presumptively fact which are stated, arise the problem statements along with questionings, which are delivered to two main questions of (1)how does American and Chinese culture shape the cultural identity of Olivia’s character in Amy Tan’s The Hundred Secret Senses? and (2) how is Hybridity reflected in Olivia’s character caused by American and Chinese culture in Amy Tan’s The Hundred Secret Senses? This study uses descriptive qualitative method, hybridity as the main theory, the concept of culture, cultural identity, Chinese and American cultural values, and orientalism as the supporting theory. Last of all, the result describes that second generation of immigrant is able to recognize the parental culture that belong to her through the cultural values of that country and another’s influence which is relates with the parent’s culture.Keywords: cultural identity, second generation, reshaping, power, hybridity